Performance Prediction of Signal Integration for Coherent MIMO Radar With Random Amplitude Errors - Wang, Mingxing; Li, Xiaolong; Chen, Desheng; Greco, Maria Sabrina; Gini, Fulvio; Yeo, Tat Soon (IEEE transactions on aerospace and electronic systems, 2025)
This article investigates the performance of coherent multiple-input multiple-out (MIMO) radar in the presence of independent but not necessarily identically distributed random amplitude errors. We first establish the coherent MIMO radar echo model that incorporates random amplitude errors. Then, to accurately assess the multichannel signal integration performance with amplitude errors, we develop closed-form solutions for the average power, processing gain, and detection probability. In addition, we provide a simplified expression of the average power in the case of independent and identically distributed (i.i.d.) errors. Further, to bridge the gap between theory and practical applications, two representative i.i.d. error distributions (uniform distribution and truncated Gaussian distribution) are examined. The average power, processing gain, and detection probability are calculated in closed form. Finally, numerical simulations confirm the validity and accuracy of closed-form analytical results.